EFFECTIVENESS OF SOCIAL MEDIA AS A MARKETING PLATFORM IN INCREASING BRAND AWARENESS AND DEVELOPING SKINCARE PRODUCT SALES AMONG MODERN SOCIETY - Pratiwi, Bella Ufi; Anisah, Hastin Umi (Penelitian dan Pengembangan Ilmu, 2024)
Interactions between companies and customers through social media have grown to be more complex, diverse, and intensive. Consumers before deciding to purchase a product, especially skincare products, will search for information on several specific skincare brands. The purpose of this study is to examine more deeply the effectiveness of social media as a marketing platform in increasing brand awareness and developing sales of skincare products in modern society. The method used in this study is a systematic literature review (SLR). The literature search was carried out with the help of the Publish or Perish application by entering the API key in the search in the Scopus section. The literature search that has been carried out obtained 200 literature findings in the range of 2019 to 2024. The results showed that social media has proven effective in increasing brand awareness and sales of skincare products in modern society.